Monopoli Dan Persaingan Usaha Dalam Perspektif Hukum Positif Dan Ekonomi Islam - Achmad Fahrur Rozzi (GLOBAL SCIENTS PUBLISHER, 2025)
Monopoly and business competition constitute two pivotal phenomena in the contemporary business landscape that exert substantial influence on market participants and consumers alike. Indonesia's Law No. 5 of 1999 governs the prohibition of monopolistic practices and anti-competitive business conduct. Under Islamic jurisprudence, monopolistic practices (ihtikar) are similarly proscribed as they contravene fundamental principles of justice and adversely affect public welfare. This study seeks to examine the conceptualization of monopoly, the framework of competition law, the underlying principles and objectives of anti-monopoly legislation, and their implementation vis-à-vis Islamic economic precepts. The research methodology adopts a qualitative approach utilizing comprehensive literature review. The findings reveal that positive legal regulations and Islamic economic principles converge in their fundamental objective of establishing an equitable and balanced marketplace.